2009
DOI: 10.1002/art.24404
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MicroRNA‐146a in osteoarthritis cartilage

Abstract: Objective. A role of microRNA, which are ϳ22-nucleotide noncoding RNAs, has recently been recognized in human diseases. The objective of this study was to identify the expression pattern of microRNA-146a (miR-146a) in cartilage from patients with osteoarthritis (OA).Methods. The expression of miR-146a in cartilage from 15 patients with OA was analyzed by quantitative reverse transcription-polymerase chain reaction (RT-PCR) and by in situ hybridization. Induction of the expression of miR-146a by cultures of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
249
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(268 citation statements)
references
References 32 publications
14
249
4
1
Order By: Relevance
“…Yamasaki et al . reported that inflammatory cytokines induced miR‐146a expression might negatively regulate catabolic factors such as MMP13 expression through miR‐146‐negative feedback including down‐regulation of IRAK1 and TRAF6 in early OA cartilage 24. A study by Bo Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yamasaki et al . reported that inflammatory cytokines induced miR‐146a expression might negatively regulate catabolic factors such as MMP13 expression through miR‐146‐negative feedback including down‐regulation of IRAK1 and TRAF6 in early OA cartilage 24. A study by Bo Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…First, the expression of miR‐146a was stimulated by inflammatory factors such as interleukin 1 and tumor necrosis factor‐alpha (Sheedy & O'Neill, 2008). It was one of the first microRNAs associated with OA cartilage (Yamasaki et al., 2009). miR‐146a operates to fine‐tune inflammatory responses via a “negative regulatory loop” (Ma, Becker Buscaglia, Barker & Li, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Yamasaki et al. observed that miR‐146a is stimulated by IL‐1 and expressed intensely in mild OA cartilage (Yamasaki et al., 2009). However, in moderate and severe OA samples, miR‐146a expression is significantly decreased, in parallel to the increase in MMP‐13 level (Yamasaki et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Abnormalities in cartilage development have been observed in Dicer gene dysfunction models, and miRNA is known to play a key role in cartilage differentiation. 3 miRNA plays a key role in differentiation and growth in organs and tissues, 2 and miRNAs expressed specifically in cartilage [4][5][6][7][8] have been reported. Till date, miR21, 4 miR22, 9 miR27a, 6 miR140, 10 and miR146 8 have been reported as miRNAs that are associated with cartilage metabolism.…”
mentioning
confidence: 99%